MRI-based mechanical analysis of carotid atherosclerotic plaque using a material-property-mapping approach: A material-property-mapping method for plaque stress analysis. (April 2023) - Mendieta, Jessica Benitez; Fontanarosa, Davide; Wang, Jiaqiu; Paritala, Phani Kumari; Muller, Juanita; Lloyd, Thomas; Li, Zhiyong
Highlights: A mapping method was proposed for computational analysis of carotid plaques. The proposed method was compared to a traditional method using patient's data. The mapping method uses the coordinates for each pixel/voxel and tissue type. The calculated stresses by the mapping method were reduced at transitional regions. Stress distribution and location of the maximum stresses tended to remain similar. Abstract: Background and objective: Atherosclerosis is a major underlying cause of cardiovascular conditions. In order to understand the biomechanics involved in the generation and rupture of atherosclerotic plaques, numerical analysis methods have been widely used. However, several factors limit the practical use of this information in a clinical setting. One of the key challenges in finite element analysis (FEA) is the reconstruction of the structure and the generation of a mesh. The complexity of the shapes associated with carotid plaques, including multiple components, makes the generation of meshes for biomechanical computation a difficult and in some cases, an impossible task. To address these challenges, in this study, we propose a novel material-property-mapping method for carotid atherosclerotic plaque stress analysis that aims to simplify the process. Methods: The different carotid plaque components were identified and segmented using magnetic resonance imaging (MRI). For the mapping method, this information was used in conjunction with an in-house code, which provided the coordinates for each pixel/voxel and tissue type within a predetermined region of interest. These coordinates were utilized to assign specific material properties to each element in the volume mesh which provides a region of transition. The proposed method was subsequently compared to the traditional method, which involves creating a composed mesh for the arterial wall and plaque components, based on its location and size. Results: The comparison between the proposed material-property-mapping method and the traditional method was performed in 2D, 3D structural-only, and fluid-structure interaction (FSI) simulations in terms of stress, wall shear stress (WSS), time-averaged WSS (TAWSS), and oscillatory shear index (OSI). The stress contours from both methods were found to be similar, although the proposed method tended to produce lower local maximum stress values. The WSS contours were also in agreement between the two methods. The velocity contours generated by the proposed method were verified against phase-contrast magnetic resonance imaging (MRI) measurements, for a higher level of confidence. Conclusion: This study shows that a material-property-mapping method can effectively be used for analyzing the biomechanics of carotid plaques in a patient-specific manner. This approach has the potential to streamline the process of creating volume meshes for complex biological structures, such as carotid plaques, and to provide a more efficient and less labor-intensive method.